2020
DOI: 10.1016/j.celrep.2020.108041
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient Strategies for Microglia Replacement in the Central Nervous System

Abstract: Highlights d mrBMT and mrPB achieve nonself microglia replacement at the CNS-wide scale d mrMT allows foreign microglia to replace endogenous cells at the specified brain region d mrBMT and mrPB cells are derived from CCR2-positive BMCs and PBCs, respectively d mrBMT and mrPB cells are more macrophage-like, while mrMT cells are more microglia-like

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 82 publications
(117 reference statements)
0
116
0
Order By: Relevance
“…One significant limitation of the traditional transplantation method is the low replacement efficiency, which may be another reason for inconsistent therapeutic outcomes of microglia transplantation or alloreplacement. In 2020, Xu et al reported three highly efficient strategies for microglia replacement globally in the CNS or in specific brain regions 141 . Compared to traditional methods, they created niches in the mouse brain that were microglia‐free, prior to non‐self cell transplantation.…”
Section: Therapeutic Opportunities and Challenges In Targeting Microgmentioning
confidence: 99%
See 1 more Smart Citation
“…One significant limitation of the traditional transplantation method is the low replacement efficiency, which may be another reason for inconsistent therapeutic outcomes of microglia transplantation or alloreplacement. In 2020, Xu et al reported three highly efficient strategies for microglia replacement globally in the CNS or in specific brain regions 141 . Compared to traditional methods, they created niches in the mouse brain that were microglia‐free, prior to non‐self cell transplantation.…”
Section: Therapeutic Opportunities and Challenges In Targeting Microgmentioning
confidence: 99%
“…These microglia‐free niches aided survival and engraftment of transplanted cells. The transplantation strategies also open up a window for treatment of microglia‐associated CNS disorders, aside from stroke 141 . Although microglia alloreplacement showed therapeutic promise, more studies are needed to understand the exact role, mechanism, and integration of grafted microglia and their impact on outcomes after stroke.…”
Section: Therapeutic Opportunities and Challenges In Targeting Microgmentioning
confidence: 99%
“…An alternative approach, of transplantation of genetically-engineered autologous hematopoietic stem cells, has proven to be beneficial in X-linked adrenoleukodystrophy [115,116]. Recently strategies for efficient microglial replacement therapy have been developed in mouse [117][118][119].…”
Section: Emerging Therapies For Crlmentioning
confidence: 99%
“…The first step of Mr MT is replacing the endogenous microglia with tamoxifen-sensitive CX3CR1-CreER::DTA microglia-like cells through Mr BMT ( Xu et al., 2020 ). For the detailed protocol of Mr BMT, please kindly refer to Xu et al.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…We hereby change the name to Mr MT. For complete details on the use and execution of this protocol, please refer to Xu et al. (2020) .…”
mentioning
confidence: 99%